Simulation of soil temperature and moisture under different snow and frost conditions with COUP model - Guitart Xarpell, Lídia; Koivusalo, Harri; Laurén, Ari; Repo, Tapani (Finnish Forest Research Institute, 2010)
The aim was to use the COUP model to simulate soil heat and water processes under different snow and soil frost conditions. The calibration data for the study was collected in a snow manipulation study in a 47-year old stand of Norway spruce located in the eastern part of Finland. The COUP model simulations were able to illustrate the typical effects of freezing and thawing in terms of soil temperature, snow cover and water content. The model was capable to produce good predictions for the control plots without any interference of the snow cover as well for artificial plots with snow cover removed. However, simulated soil frost depth and water balance had some lacks in their predictions. One source of error relied in the meteorological input data, because the precipitation and relative humidity time series were not considered to be well representative of the study area. In addition, the model results were likely affected by the net radiation and cloudiness data, which were measured away from the study site. More measurement points in each plot and at different depths could aid in a more detailed calibration of the model. Despite these deficiencies the dataset as a whole met quite well the model input requirements. Essential parameters that the model needs to run can be readily determined and easily introduced in the model. The simulations can be further improved through some changes in the calibration process and/or through validating the model with additional independent data. In conclusion, the COUP model proved to be a functional tool for the simulation of heat and water soil processes. It is easy to manage, well organized and capable to simulate a range of soil situations by defining only few parameters and conditions.
Keywords: COUP-malli; ilmastomuutos; juuret; kuusi; lumipeite; maan kosteus; maan lämpötila; mallinnus; routa; simulointi; climate change; COUP; modelling; Norway spruce; precipitation; snow cover; soil frost; soil moisture; soil temperature